Monoamine Oxidase Inhibition by Plant-Derived β-Carbolines; Implications for the Psychopharmacology of Tobacco and Ayahuasca - Berlowitz, Ilana; Egger, Klemens; Cumming, Paul (Frontiers in Pharmacology, 2022)
The monoamine oxidases (MAOs) are flavin-containing amine oxidoreductases responsible for metabolism of many biogenic amine molecules in the brain and peripheral tissues. Whereas serotonin is the preferred substrate of MAO-A, phenylethylamine is metabolized by MAO-B, and dopamine and tyramine are nearly ambivalent with respect to the two isozymes. β-Carboline alkaloids such as harmine, harman(e), and norharman(e) are MAO inhibitors present in many plant materials, including foodstuffs, medicinal plants, and intoxicants, notably in tobacco (Nicotiana spp.) and in Banisteriopsis caapi, a vine used in the Amazonian ayahuasca brew. The β-carbolines present in B. caapi may have effects on neurogenesis and intrinsic antidepressant properties, in addition to potentiating the bioavailability of the hallucinogen N,N-dimethyltryptamine (DMT), which is often present in admixture plants of ayahuasca such as Psychotria viridis. Tobacco also contains physiologically relevant concentrations of β-carbolines, which potentially contribute to its psychopharmacology. However, in both cases, the threshold of MAO inhibition sufficient to interact with biogenic amine neurotransmission remains to be established. An important class of antidepressant medications provoke a complete and irreversible inhibition of MAO-A/B, and such complete inhibition is almost unattainable with reversible and competitive inhibitors such as β-carbolines. However, the preclinical and clinical observations with synthetic MAO inhibitors present a background for obtaining a better understanding of the polypharmacologies of tobacco and ayahuasca. Furthermore, MAO inhibitors of diverse structures are present in a wide variety of medicinal plants, but their pharmacological relevance in many instances remains to be established.